THE HARMONY OF HISTORICAL TRUTH AND ARTISTIC TEXTILE IN THE NOVELS " THE SCORPION FROM THE ALTAR " AND "DECLINE" (Scientific journal of the Fergana State University, 2024)
This article examines the development of events, the harmony of the system of proportional images in the pentalogy "Decline" by the son of Sadikhan Mavlavikhan and the novel "Scorpion from the Altar" by Abdulla Qadiri. Also, this analysis is based on historical-scientific works and works of this period. In other words, since the events of the same period are covered in both novels, the similarities between the two works were comparatively analyzed. Also, the level of compatibility of this aspect with literature and history, the proportionality of historical truth and artistic fabric was also checked. Similarity and dissimilarity of images in two works, their characteristics are analyzed in parallel.